2011
DOI: 10.4253/wjge.v3.i7.145
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel endoscopic manipulation system: The Endoscopic operation robot

Abstract: The study suggested the possibility of the clinical application of the EOR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…This hesitation was caused, at least partially, by technical reasons: in early surgical robotic systems, haptic feedback was either patched on or estimated/simulated, the performance of which was rather limited, hence surgeons were less in favor of the outcomes [48]. However, with the fast developments in robotic technology, recent surgical systems with haptic feedback are equipped with new force sensors and very well implemented control [52,53], and as a result, more and more studies showed that haptic feedback became one of the most wanted features for the next generation of surgical robots [54][55][56][57][58][59].…”
Section: Innovations For Hapticsmentioning
confidence: 99%
“…This hesitation was caused, at least partially, by technical reasons: in early surgical robotic systems, haptic feedback was either patched on or estimated/simulated, the performance of which was rather limited, hence surgeons were less in favor of the outcomes [48]. However, with the fast developments in robotic technology, recent surgical systems with haptic feedback are equipped with new force sensors and very well implemented control [52,53], and as a result, more and more studies showed that haptic feedback became one of the most wanted features for the next generation of surgical robots [54][55][56][57][58][59].…”
Section: Innovations For Hapticsmentioning
confidence: 99%
“…Despite intuitive and ergonomic shortcomings of the conventional endoscope, experts are competent in scope manipulation without causing excessive patient pain [13,42]. Previous studies showed that remote actuation platforms could not yet compete with the efficiency of conventional endoscope control [38,62,71]. The setup of these platforms prevented adequate scope manipulation [62,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Previously introduced robotic designs provide single-person control of multiple steerable instruments [21,23,37,71,75]. However, none of these systems have also proven the essential versatility to arrive at intervention sites that are difficult to reach in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Its application in therapeutic procedures has not been tested. Although the authors suggest the possibility of clinical application of the system, it is far from being ready for clinical implementation [Kume et al, 2011]. [Kume et al, 2011] All described systems are mainly developed to assist in navigating the lumen in diagnostic procedures.…”
Section: Related Workmentioning
confidence: 99%
“…Although the authors suggest the possibility of clinical application of the system, it is far from being ready for clinical implementation [Kume et al, 2011]. [Kume et al, 2011] All described systems are mainly developed to assist in navigating the lumen in diagnostic procedures. A system that assists in performing advanced therapeutic procedures by robotizing all degrees of freedom of a flexible endoscope, and that is steered with one hand, does not exist.…”
Section: Related Workmentioning
confidence: 99%